Analisis Perlakuan Akuntansi Atas Selisih Kurs Dan Transaksi Dalam Mata Uang Asing Serta Pengaruhnya Terhadap Laporan Keuangan PT Fks Food Sejahtera - Uslifa Nurfagfira; Arif Kurniawan; Rio Rohman Saputra; Endang Kartini Panggiarti (Universitas Katolik Widya Karya Malang, 2024)
The purpose of this article is to analyze the treatment of foreign exchange differences and foreign currency transactions at PT FKS Food Sejahtera. At PT FKS Food Sejahtera, exchange rate differences and foreign currency transactions arise from overseas subsidiaries, loans, export sales, and various costs of the company's main purchases. The method used in this research is qualitative research, where PT FKS Food Sejahtera is the object of research. Information and data collection were obtained from literature studies and previous articles related to this topic, as well as PT FKS Food Sejahtera data taken from the annual report of PT FKS Food Sejahtera. The results showed that the treatment of foreign exchange differences and transactions in foreign currencies carried out by PT FKS Food Sejahtera was in accordance with the current PSAK.